2011
DOI: 10.1016/j.jip.2010.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the reproductive biology of Biomphalara glabrata infected with different doses of Echinostoma paraensei miracidia

Abstract: The egg-laying rate, number of egg masses, number of eggs/mass, number of eggs hatched/snail and egg viability of Biomphalaria glabrata exposed to different doses (5 and 50) of Echinostoma paraensei miracidia were analyzed as indicators of reproductive activity. Polystyrene plates were placed in aquariums containing the snails and every other day for four weeks after infection the plates were removed to count the number of egg masses and eggs laid. After this, the plates were numbered individually and placed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Then the egg masses were observed to count the snails hatching. The egg viability, expressed as a percentage, is the number of snails hatched divided by the number of eggs laid in each experimental group, multiplied by 100 (Tunholi et al, 2011).…”
Section: Analysis Of the Reproductive Biology Of B Glabrata Infectedmentioning
confidence: 99%
See 1 more Smart Citation
“…Then the egg masses were observed to count the snails hatching. The egg viability, expressed as a percentage, is the number of snails hatched divided by the number of eggs laid in each experimental group, multiplied by 100 (Tunholi et al, 2011).…”
Section: Analysis Of the Reproductive Biology Of B Glabrata Infectedmentioning
confidence: 99%
“…So, understanding the changes in the reproductive biology of snails infected with A. cantonensis is essential for developing effective methods against the spread of human eosinophilic meningoencephalitis. However, it is surprising that studies of the reproductive activity of A. cantonensis-infected snails have not yet been conducted, since this parasite has great importance to public health and the response to infection is highly variable among snail species infected by different helminths (Tunholi et al, 2011). To shed light on this subject, the present study analyzed for the first time, the changes in the reproductive biology of Biomphalaria glabrata caused by infection by A. cantonensis during its prepatent period (3 weeks of infection) (Guilhon and Gaalon, 1969), using the parameters total number of eggs, number of egg masses, number of eggs/mass, number of eggs/ snail, percentage of viable eggs, and galactogen content in albumen gland, as well as the histological status of the gonad (ovotestis of infected snails).…”
Section: Introductionmentioning
confidence: 99%
“…Limited reproductive capacity of the parasite may have occurred in the present study, which was possibly inluenced by factors such as nutrient availability and physical space for cercariogenesis (TUNHOLI ET AL., 2011a;2011b).…”
Section: Discussionmentioning
confidence: 99%
“…In this fashion, infected snails begin to use non-carbohydrate sources to survive and reproduce, resulting in many physiological alterations (Pinheiro et al 2009) and a process of compensatory fecundity as observed in the E. paraensei-B. glabrata model (Tunholi et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…mansoni with different miracidial doses observed that snails subjected to plurimiracidial infections showed smaller digestive gland relative to infected snails with a low parasitic load, indicating a balance of space and energy between the development of the parasite/host. In this context, our group observed that, although changes in the reproductive profile of B.glabrata infected with E. paraensei occur, this was independent of the miracidial dose used (Tunholi et al 2010).…”
Section: Introductionmentioning
confidence: 89%